Quantum theory of electronic excitation and sputtering by transmission electron microscopy. Issue 3 (15th June 2022) - Yoshimura, Anthony; Lamparski, Michael; Giedt, Joel; Lingerfelt, David; Jakowski, Jacek; Ganesh, Panchapakesan; Yu, Tao; Sumpter, Bobby G.; Meunier, Vincent
Abstract : Combining quantum electrodynamics with density functional theory, we model electronic excitation and sputtering by beam electrons in two-dimensional materials. Electronic excitations can drastically increase the sputtering rates in these materials. Abstract : Many computational models have been developed to predict the rates of atomic displacements in two-dimensional (2D) materials under electron beam irradiation. However, these models often drastically underestimate the displacement rates in 2D insulators, in which beam-induced electronic excitations can reduce the binding energies of the irradiated atoms. This bond softening leads to a qualitative disagreement between theory and experiment, in that substantial sputtering is experimentally observed at beam energies deemed far too small to drive atomic dislocation by many current models. To address these theoretical shortcomings, this paper develops a first-principles method to calculate the probability of beam-induced electronic excitations by coupling quantum electrodynamics (QED) scattering amplitudes to density functional theory (DFT) single-particle orbitals. The presented theory then explicitly considers the effect of these electronic excitations on the sputtering cross section. Applying this method to 2D hexagonal BN and MoS2 significantly increases their calculated sputtering cross sections and correctly yields appreciable sputtering rates at beam energies previously predicted to leave the crystals intact. The proposed QED-DFT approach can be easily extended to describe a rich variety of beam-driven phenomena in any crystalline material.